2021
DOI: 10.1111/tpj.15447
|View full text |Cite
|
Sign up to set email alerts
|

Glyoxalase I‐4 functions downstream of NAC72 to modulate downy mildew resistance in grapevine

Abstract: Summary Glyoxalase I (GLYI) is part of the glyoxalase system; its major function is the detoxification of α‐ketoaldehydes, including the potent and cytotoxic methylglyoxal (MG). Methylglyoxal disrupts mitochondrial respiration and increases production of reactive oxygen species (ROS), which also increase during pathogen infection of plant tissues; however, there have been few studies relating the glyoxalase system to the plant pathogen response. We used the promoter of VvGLYI‐4 to screen the upstream transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…The endoplasmic reticulum stress response regulator NAC089 acts as an ER stress‐mediated immunity (ERSI) regulator to actively regulate programmed cell death (PCD), thereby preventing pathogen infection (Ai et al 2021). Grape VvNAC72 negatively regulates the detoxification of methylglyoxal by inhibiting VvGLYI‐4 and ultimately enhances the resistance to downy mildew (Li et al 2021). However, we found that MnNAC100 may reduce plant resistance by suppressing the expression of downstream resistance genes.…”
Section: Discussionmentioning
confidence: 99%
“…The endoplasmic reticulum stress response regulator NAC089 acts as an ER stress‐mediated immunity (ERSI) regulator to actively regulate programmed cell death (PCD), thereby preventing pathogen infection (Ai et al 2021). Grape VvNAC72 negatively regulates the detoxification of methylglyoxal by inhibiting VvGLYI‐4 and ultimately enhances the resistance to downy mildew (Li et al 2021). However, we found that MnNAC100 may reduce plant resistance by suppressing the expression of downstream resistance genes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the differentially expressed transcription factors identified in response to ethylene treatment included NAC72, NAC100, ERF92, RAP2-2, bHLH63, and bHLH130. Grapevine VvNAC72 negatively modulates detoxification of methylglyoxal through repression of VvGLYI-4, thus enhancing resistance to downy mildew [42]; ghr-miR164 can also directly cleave GhNAC100 mRNA in the post-transcriptional process to positively regulate Verticillium dahliae resistance [43]. ERF92 is selective for temperature stress tolerance in peas (Pisum sativum L.) [44].…”
Section: Degs Of Transcription Factorsmentioning
confidence: 99%
“…It is characterized by a conserved NAC domain at the N‐terminus and a diverse transcriptional regulatory region at the C‐terminus (Olsen et al, 2005). NACs have important roles in a variety of developmental processes (Mao et al, 2017; Fang et al, 2020; Mao et al, 2020) and biotic (Li et al, 2021; Meng et al, 2022; Bi et al, 2023) and abiotic stress responses (Hu et al, 2006; Zheng et al, 2009; Nakashima et al, 2012; Xiang et al, 2021a, 2021b). Overexpressing sweet potato IbNAC7 in Arabidopsis increases salt tolerance by activating reactive oxygen species (ROS) scavenging and affecting the transcription of stress‐related genes (Meng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%